TAIWAN POLITICAL PATTERN AND GEOPOLITICAL WEAKNESS: IMPLICATIONS FOR TAIWAN TO SEE THE INTERACTION BETWEEN THE CROSS-STRAIT-RELATIONS AND SINO-RUSSIAN RELATIONS UNDER THE THEME OF SHANGHAI COOPERATION ORGANIZATION (SCO) - Hu Feng-Yung (Сравнительная политика, 2015)
Taiwan media reflects the diversity and chaos of Ideology after the political reform from the end of 1980’s when the leader of Taiwan Chiang Ching-kuo announced the lifting of martial law on July 15, 1987. The democracy promoted the exchanging situation between Taiwan and Mainland China. The importance of Taiwan’s geopolitical position is disappearing by time. To integrate into the broadened AsianPacific region in the era of China’s uprising and Taiwan’s closed economic cooperation with Mainland China under its military threat is a new trend for Taiwan’s foreign policy. With the returning back of Putin to the presidency of Russia and his Asian cooperation strategy, Taiwan could understand the role of Russia appropriately to think about how to participate in this regional cooperation and consolidate the national security in the cross-strait region. The attitude of Russia toward the SCO should be paid attention to from the side of Taiwan authority. The author found that in the bigger geopolitical pattern in Asian-Pacific region that Russia plays more and more stable and positive role in the regional security under the competition with USA. The competition between USA and Russia is the new world geopolitical pattern for both Taiwan and Mainland China. This paper is divided into two parts from the aspect of Taiwan political and geopolitical changes to examine the problems of the cross-strait relations and SinoRussian relations under the theme of SCO in East Asia. The author assumes that Russia’s Asian Strategy will strengthen Russia’s influence on the cross-strait relations deeply and Russia will play the more and more important role in regional security and economic cooperation in East Asia.